Recreating “Holy Simplicity”’. Romanian Renditions of Jacques Prévert’s Alicante - Măciucă, Gina (Stylistyka, 2021)
While still under the spell of Jacąues Prevert’s intriguingly unsophisticated Alicante, and in relentless pursuit of uncovering novel strategies for creating literary beauty, I decided to subject the poem to a minutę scrutiny in the hope of ferreting out the secret stuff “holy simplicity” is madę of. Much to my surprise, “lurking” behind this sancta simplicitas I fo- und a fine network of complex pattems, each carefully designed to interact with the rema- inder in a flawless manner, thus considerably enhancing the potency of the ensemble. The following are several of the major pattems involved: dichotomous partition into sexuality and spirituality; colour-related symbolism; word play; dual-nature semantic pattem of keywords (signalling interweaving of libido-related and spirit-related zones); interplay of inherent and non-inherent readings of adjectives, of regular and irregular rhymes, or of verses with different-numbered feet (even and odd); effective intermingling of lexemes which synergetically appeal to four human senses.In the second phase, my research was steered away from fathoming the miracle of creating “holy simplicity” towards investigating the sustained toil of recreating it in a diffe- rent language: Romanian. The two subsections devoted to the topie in question submit to the reader Gellu Naum’s translation of Alicante, and the one originating with nonę other than the author of this contribution respectively. A brief comparison of the two renditions has yielded the following points of dissimilarity: a) Naum’s is a true-to-spirit translation, whereas minę has been created with the genius of the target language in mind. Herefrom stem the main contrasts listed below. b) Naum keeps on the fruit (Fr signifier orange, Rom signifierportocala), while I madę so bold as to replace it by the equally exotic mango for reasons specified under 111.2 below (s. also substitution of noptiera (= bedside ta- ble) and dormitory (= bedroom) for masa (Fr table) and pat (Fr lit) respectively. c) Naum completely disregards the pun in linę 4, whereas I did not think twice about slightly modi- fying the rhythmic pattem in order to be able to render the former into Romanian.d) Likewise, Naum translates in utter defiance of the rhyming pattem, whereas to me ob- serving it is a matter of prime importance.Needless to say, I am quite willing to take both the blame and the credit - if any — for the vast array of meanings I took the liberty to read into Prevert’s poem, as well as for the translational licences resorted to in the hope of successfully putting these unique connota- tions across to the reader.The concluding section discusses still a further possibility of recreating Prevert’s Alicante, namely by setting it to musie. In this respect, Chuck Perrin’s rendition has the ad- ded advantage of enhancing its lyricism, while concurrently taking the poem to that ma- gical space hovering above the spiritual.